PROBLEMS OF NATIONAL TAX PLANNING - Kalambet, S. V.; Pieshykov, H. R. (Science and Transport Progress, 2008)
The matter and contents of the planning of state tax policy have been analysed, the place of control of tax risks as the integral part of the tax management is reflected.